KONTRIBUSI MATA PELAJARAN RENCANA ANGGARAN BIAYA (RAB) TERHADAP KEBERHASILAN PELAKSANAAN PROGRAM PRAKTEK KERJA INDUSTRI KELAS XI TEKNIK GAMBAR BANGUNAN SMK NEGERI 1 BUKITTINGGI - 515-524 , Nofri Wahyudi (Universitas Negeri Padang, 2014)
Abstract This research is based on poor result of budgeting plan subject in SMKN 1 Bukittinggi that is below minimum completeness criteria (KKM) 75. The success of field work or PRAKERIN is supported by one of subject that is RAB. Therefore, it is suggested a proposal of hypothesis that is: there is a contribution of budgeting plan subject (RAB) toward achievement of industrial field work in XI class construction drawing SMKN 1 Bukittinggi. Population in this research was students of XI class construction drawing program SMKN 1 Bukittinggi that amounted to 51 students. Sampel collection technique in this research was total sampling. Research instrument was questionnaire with Likert scale 4 stage modification for questionnaire that had been validated its reliability. Data analysis technique was correlation technique. Result of data analysis showed that correlation between RAB learning and achievement of industrial field work with Pearson Correlation 0.408 was given contribution of 16.65%. Keywords: Contribution, budgeting plan subject, field work.